Aesthetics, disinterestedness, and effectiveness in political art - Asavei, Maria Alina (Lexington Books, 2018)
This book's main claim is that political art should not disregard questions of aesthetic reception and value. It argues that some neglected aspects of traditional aesthetics actually enhance the relationship between art and politics more than contemporary art theorists are keen to admit.